Pengaruh Style Leadership Terhadap Work Performance Melalui Work Motivation Sebagai Variabel Intervening - Pertiwi, Nabillah Bella; Nahirsah, Ezzah; Hafas, Hafriz Rifki (Journal of Management and Economics Research, 2023)
This study aims to determine the effect of leadership style on work performance through work motivation at the Sumatra Provincial General Bureau Office. The total population in this study amounted to 103 people, and by using a saturated sampling technique, a sample of 103 people was obtained. The analysis technique used is path analysis.The results showed that there was no influence of leadership style on work performance because the value of Sig.of 0.906 > 0.05.There is a significant influence of leadership style on work performance through work motivation because the value of Sig.of 0.000 < 0.05.